A Review On Electrospun Short Fiber Production - Raja, Cheryl Rinai; Sawawi, Marini; Sahari, Siti Kudnie; Andrew, Magdalene; Fun, Chin Suk (International Journal of Integrated Engineering, 2023)
Nanotechnology has become the interest of researchers in recent years for their unique properties of submicron scale materials. Nanotechnology also consists of nanofibers made from natural or synthetic polymers which can be electrospun into ultra-thin continuous fibers. These nanofibers are versatile as it can be found in various applications such as in filtration, affinity membranes, tissue engineering, biosensors, scaffolds, drug delivery and fiber reinforcement. Over the years, many researchers have reported various methods used to produce short electrospun fiber by means of ultrasonication, mechanical cutting, UV cutting, precipitation method, microtome cutting, cryo-microcutting, cryogenic milling, ball milling, and razor blade cutting under liquid nitrogen. The aim of this paper is to provide a review on electrospun short fiber production which elaborates more on the scission methods of the continuous as-spun fibers. The literature shows that several methods have been proposed and utilized, with varying degrees of success. Overall, it can be concluded that further research is needed to fully understand the complexities of this area and to develop a more effective approach.